2015
DOI: 10.1097/gme.0000000000000272
|View full text |Cite
|
Sign up to set email alerts
|

Can the FRAX tool be a useful aid for clinicians in referring women for periodontal care?

Abstract: Postmenopausal women whose FRAX scores suggest major OPF risk have significantly more severe periodontitis endpoints than controls even though oral hygiene scores do not significantly differ. These findings suggest to clinicians treating women after menopause that referral to a periodontist for disease screening may be appropriate for those women with high fracture risk based on FRAX scores.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…FRAX involves several clinical risk factors to predict the skeletal condition (Kanis et al 2013). The association of severe periodontal disease with low BMD or FRAX was reported previously (Alli et al 2015).…”
Section: Discussionmentioning
confidence: 89%
“…FRAX involves several clinical risk factors to predict the skeletal condition (Kanis et al 2013). The association of severe periodontal disease with low BMD or FRAX was reported previously (Alli et al 2015).…”
Section: Discussionmentioning
confidence: 89%
“…Several studies have focused on the association between chronic periodontitis and osteoporosis, and systematic reviews indicate that postmenopausal women with osteopenia or osteoporosis have more severe periodontitis [ 5 , 6 ]. Higher FRAX scores have been associated with impaired periodontal status in postmenopausal women [ 7 ], and Penoni et al also found in a later study that periodontal disease was not a predictor for osteoporosis, although FRAX was “a useful tool to suggest periodontal evaluation” [ 8 ]. In another study, Priebe et al found an association between the number of missing teeth, hip fractures, and a FRAX assessment of fracture risk [ 9 ].…”
Section: Introductionmentioning
confidence: 99%